Large-eddy simulation of dense gas dispersion over a simplified urban area. (March 2017) - Wingstedt, E.M.M.; Osnes, A.N.; Åkervik, E.; Eriksson, D.; Reif, B.A. Pettersson
Abstract: Dispersion of neutral and dense gas over a simplified urban area, comprising four cubes, has been investigated by the means of large-eddy simulations (LES). The results have been compared to wind tunnel experiments and both mean and fluctuating quantities of velocity and concentration are in very good agreement. High-quality inflow profiles are necessary to achieve physically realistic LES results. In this study, profiles matching the atmospheric boundary layer flow in the wind tunnel, are generated by means of a separate precursor simulation. Emission of dense gas dramatically alters the flow in the near source region and introduces an upstream dispersion. The resulting dispersion patterns of neutral and dense gas differ significantly, where the plume in the latter case is wider and shallower. The dense gas is highly affected by the cube array, which seems to act as a barrier, effectively deflecting the plume. This leads to higher concentrations outside of the array than inside. On the contrary, the neutral gas plume has a Gaussian-type shape, with highest concentrations along the centreline. It is found that the dense gas reduces the vertical and spanwise turbulent momentum transport and, as a consequence, the turbulence kinetic energy. The reduction coincides with the area where the gradient Richardson number exceeds its critical value, i.e. where the flow may be characterized as stably stratified. Interestingly, this region does not correspond to where the concentration of dense gas is the highest (close to the ground), as this is also where the largest velocity gradients are to be found. Instead there is a layer in the middle of the dense gas cloud where buoyancy is dynamically dominant. Highlights: Dense gas dispersion was modeled with variable density, large-eddy simulation. High-quality inflow profiles were generated in precursor simulations. Results compare excellently to wind tunnel experiments. Dense gas significantly alters the flow field yielding a wider and shallower plume. Stably stratified region does not coincide with maximum concentration.